Editorial: Modified Theories of Gravity and Cosmological Applications—Topical Collection - Panayiotis Stavrinos; Emmanuel N. Saridakis (Universe)
General relativity (GR) has been remarkably successful in describing the gravitational interaction through the curvature of spacetime [...]